2011
DOI: 10.1007/s12663-011-0325-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Intralesional Sclerotherapy with Sodium Tetradecyl Sulfate Versus Bleomycin in the Management of Low Flow Craniofacial Soft Tissue Vascular Lesions

Abstract: Objective Comparison of the efficacy of bleomycin over sodium tetradecyl sulfate (STS) when given intralesionally in the treatment of oral and maxillofacial venous malformation. Methods 16 patients with venous malformation in craniofacial region were randomly divided into two groups of eight. Group 1 was given intralesional injection of bleomycin and group 2 was injected with STS. All the cases were evaluated for a minimum period of two and a maximum of 3 years. Results Efficacy of bleomycin was found to be su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 21 publications
2
15
0
Order By: Relevance
“…The published imaging and clinical ORR for VMs of the head and neck treated with bleomycin percutaneous sclerotherapy range from 65% to 100% . The ORR in our case series (87.5%) was similar.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…The published imaging and clinical ORR for VMs of the head and neck treated with bleomycin percutaneous sclerotherapy range from 65% to 100% . The ORR in our case series (87.5%) was similar.…”
Section: Discussionsupporting
confidence: 73%
“…Our 50% complication rate, all of which were grade I or II, seems high in comparison. However, structures outside the airway represent the majority of head‐and‐neck bleomycin VMPS treatment sites in the published literature . All four of our complications after bleomycin sclerotherapy involved the oral cavity.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Sodium tetradecyl sulphate is another commonly used sclerosant and is considered the first choice for VM treatment in many centers . Nevertheless, Bajpai and colleagues reported that sodium tetradecyl sulphate is less effective than bleomycin and that complications, although minor, occur more frequently.…”
Section: Discussionmentioning
confidence: 99%